Examining the effects of frustration on working memory capacity. Issue 1 (23rd July 2019) - Fillauer, Jonathan Parks; Bolden, Jennifer; Jacobson, Melanie; Partlow, Brock H.; Benavides, Andrea; Shultz, Jessica N.
Summary: The present study attempts to expand our understanding of frustration, clinical symptoms, and working memory by examining the unique contribution of attention‐deficit/hyperactivity disorder symptoms and frustration to working memory capacity (WMC). A factor‐analytic framework was utilized to isolate and examine WMC based on results from three working memory tasks that were administered in counterbalanced order to control for individual differences in baseline WMC. All participants provided subjective ratings of frustration both prior to and after administration of a frustration induction. Results suggest that although we were able to systematically induce subjective frustration for participants in the experimental group relative to the control group, WMC was not associated with induced frustration in the present study. Results also indicated that inattention symptoms predicted baseline frustration levels. This work highlights the need to examine the extent to which storage/rehearsal WMC and additional process‐oriented working memory‐related performance variables are related to frustration. The data that support the findings of this study are available from the corresponding author upon request.